2004
DOI: 10.1890/01-6028
|View full text |Cite
|
Sign up to set email alerts
|

Riverine Organic Matter Composition as a Function of Land Use Changes, Southwest Amazon

Abstract: Abstract. We investigated the forms and composition of dissolved and particulate organic matter in rivers of the Ji-Paraná Basin, which is situated at the southern limit of the Amazon lowlands and has experienced extensive deforestation in the last three decades (ϳ35 000 km 2 ). Our objective was to investigate how extensive land-use changes, from forest to cattle pasture, have affected river biogeochemistry. We measured a series of chemical, biochemical, and isotopic tracers in three size classes of organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 37 publications
3
30
1
2
Order By: Relevance
“…C : N ratios of phytoplankton, soil, and leaves range between 5-8, 10-27, and 21-106, respectively (Hedges et al 1986;Trumbore 1993;Devol and Hedges 2001). The d 13 C of C 3 plants range from 226% to 231%, whereas C 4 grasses found on floodplains and in pastures are more enriched (212% to 216% [Hedges et al 1986;Bernardes et al 2004;Mayorga et al 2005a]). The d 13 C of phytoplankton range from 230% to 245% in rivers and lakes (Araujo-Lima et al 1986;Hedges et al 1986;Mayorga et al 2005a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C : N ratios of phytoplankton, soil, and leaves range between 5-8, 10-27, and 21-106, respectively (Hedges et al 1986;Trumbore 1993;Devol and Hedges 2001). The d 13 C of C 3 plants range from 226% to 231%, whereas C 4 grasses found on floodplains and in pastures are more enriched (212% to 216% [Hedges et al 1986;Bernardes et al 2004;Mayorga et al 2005a]). The d 13 C of phytoplankton range from 230% to 245% in rivers and lakes (Araujo-Lima et al 1986;Hedges et al 1986;Mayorga et al 2005a).…”
Section: Resultsmentioning
confidence: 99%
“…The d 13 C of phytoplankton range from 230% to 245% in rivers and lakes (Araujo-Lima et al 1986;Hedges et al 1986;Mayorga et al 2005a). The d 13 C of soil generally spans the range of the vegetation types (Bernardes et al 2004). …”
Section: Resultsmentioning
confidence: 99%
“…Boschker et al (1995) apply such methodologies in Lake Gooimer, and Marchand et al (2005) apply a similar approach to study the sediment in a mangrove system. Relatively comprehensive studies using multiple markers are reported in the Amazon system (Bernardes et al, 2004;Hedges et al, 1994). It must be pointed out that due to the complexity of the composition/source terms of organic matter and the biogeochemical evolvement they undergo in the estuarine environments, such multiple markers are important because each individual marker may be subject to limitations.…”
mentioning
confidence: 99%
“…The area of each watershed and land cover data were obtained using remote sensing techniques combined with geographic information systems described in Bernardes et al (2004). The only exception to this procedure was the Óbidos sampling site on the Amazon River, where we assumed that the percentage deforested area was the same as for the Brazilian Amazon estimated by Instituto Nacional de Pesquisas Espaciais (INPE).…”
Section: Methodsmentioning
confidence: 99%